Role of Relational Trust on Customer Behavioural Intentions: Evidence from Kenya's Banking Sector - Mutuku, Benedict; Iravo, Mike; Omwenga, Jane (Journal of Marketing and Consumer Research, 2016)
Increasing competiveness among service firms fueled by globalization have made it increasingly imperative for service firms to place emphasis on relationship marketing activities that enhance long-term relationships with profitable customers at the expense of attracting of new customers. The challenge is even bigger for Kenya's financial services sector where bank products remain thinly differentiated, shifting competition to other areas that target to cultivate customer loyalty. Thus, the purpose of this study was to examine the role of relational trust, considered as an antecedent of relationship marketing quality on customer behavioural intentions in Kenya's banking sector. Utilizing a descriptive survey research design and adapted measures of relational trust and behavioural intentions on a sample of 334 bank account holders from 43 commercial bank branches in Mombasa, Kenya, the study establishes the most important dimension of trust in the study's context is customer's trust in the bank. Trust in the bank as a brand is a most significant factor in driving their loyalty to the bank, repurchase intention, willingness to pay a higher price for the bank's services over others and a tendency to recommend it to surrounding people. Thus, strategies for building trustworthiness, supported by customer loyalty as a desirable outcome, can be seen as a method for creating a competitive advantage for service organisations.
Keywords: Relational Trust; Bank; Trust Employee Trust; Behavioural Intentions.